Negotiating counterstrategies against the far right in Cottbus, Germany: shifting relations between the state and civil society - Gala Nettelbladt (Territory, Politics, Governance, 2023)
This article examines how democratic actors from the state and the realms of civil society and the private sector form alliances to negotiate local counterstrategies against contemporary far-right contestations. It attends to two blind spots in the existing discussions about cities as bulwarks against the global rise of the far right. First, while much scholarly attention is paid to the heterogeneity of progressive civil society movements in this fight, state–civil society relations are understudied. Second, local contexts where far-right actors have already gained significant power are seldomly examined. Based on an explorative case study in the peripheral city of Cottbus, Germany – known as a hotspot of far-right organising – the article uses the Gramscian notion of the `integral state' to analyse how actors come together and how this process is marked by contentious problematisations, positionalities and motivations. The discussion reveals that the state becomes a contested terrain in these negotiations as the far right's success does not leave municipal institutions untouched. While this weakens traditional democratic state–civil society alliances, it also enables the building of new ones as community activists' perspectives shift from a position of resistance towards (cautious) partnership with the state. To conclude, I discuss the political implications of these findings.
Keywords: 320; cities; civil society; counterstrategies; far-right politics; Germany; Gramsci; local state; urban governance